Association of plasma iron with the risk of incident cancer in Chinese adults with hypertension: a nested case-control study - Zhu, Hehao; Wei, Yaping; He, Qiangqiang; Song, Yun; Liu, Lishun; Sun, Yong; Zhang, Hao; Guo, Huiyuan; Xu, Xiping; Wang, Binyan (Frontiers in Oncology, 2023)
Background: Iron is an essential element for organismal health but excessive iron is potentially toxic. However, few observational studies link plasma iron (PI) concentrations and cancer risk, and the results are inconsistent.Objective: This study aimed to explore the associations of PI concentrations with cancer risk in Chinese adults with hypertension.Methods: We conducted a nested, case-control study, including 223 pairs of incident cancer cases and matched controls from the China Stroke Primary Prevention Trial. The median time between blood sample collection and subsequent cancer event occurrence was 2.13 years. The odds ratio (OR) and 95% confidence interval (CI) for the risk of cancer by PI were estimated from multivariable conditional logistic regression models.Results: There was a nonlinear association between PI concentrations and total cancer risk. When compared with participants in tertile 2 of PI, the ORs of total cancer were 2.17 (95%CI: 1.25-3.85) and 1.29 (95%CI: 0.77-2.19) in participants in PI tertiles 3 and 1, respectively. Furthermore, higher PI was associated with increased digestive system cancer risk (OR=3.25, 95%CI:1.29-8.90), while lower PI was associated with increased risk of non-digestive system cancer (OR=3.32, 95%CI: 1.39-8.71). In a sensitivity analysis, the increases in total cancer risk or digestive system cancer risk were still observed with higher PI after excluding cancer cases occurring within the first year.Conclusions: Our results showed an increased risk of cancer related to higher PI or lower PI in Chinese adults with hypertension. Higher iron levels were linked to an increased risk of digestive system cancers, whereas lower iron levels were linked to an increased risk of non-digestive system cancers.